IRAQ TELEVISION AND THE PROBLEM OF EMERGENCY PROGRAMS : (An Analytical Study of Emergency Programs in Iraq TV) - Al-Naas, Abdul-Razaq (ALBAHITH ALALAMI, 2005)
The success of any media work in our contemporary life is based on proper planning. Television in Iraq is like any media outlet that adopts clear planning and programming in order to achieve the goals set in the news, entertainment, education. Iraq TV relies on four programming plans in one year (short term), but we often receive central instructions directly from the Minister of Information ordering to cancel the program plan and what was scheduled for broadcast to be finally replaced by alternative or emergency program associated with an incident, occasion or important news, these programs are all called (emergency programs).In this present research we will be dealing with these programs as well as the extent of their impact on the progress of planning programs in Iraqi TV. We have divided this research into an introduction, three main topics and a conclusion:First topic: TV in Iraq ... The emergence and developmentSecond topic: Media planning and the problem of program planning in Iraq TVThird topic: An analytical study of emergency programs in Iraq TV for two programs from 01/07/2002 to 30/9/2002 and from 01/10/2002 to 31/12/2002.Conclusion: We will highlight the most important findings we reached.